Pengaruh Sikap dan Norma Subjektif Terhadap Niat Menabung Pada Lembaga Perkreditan Desa (LPD) Kuwum Tabanan - Wulandari, Ni Luh Putu Sintya; Abiyoga Wulandari, Ni Luh Adisti; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of subjective attitudes and norms on people's saving intentions at the Kuwum Village Credit Institution in Tabanan.The total population of the study was 1,747 people and a sample of 95 people using the slovin technique where the method of determining the sample was using probability sampling technique with simple random sampling. The data analysis technique used is the research instrument test, namely the validity test and reliability test, classical assumption test and multiple linear regression analysis (t test and F test).Based on the results of the analysis, it was found that: 1. Attitude has a positive and partially significant effect on saving intentions. 2. Subjective norms have a positive and partially significant effect on the intention to save. 3. Attitudes and subjective norms have a positive and significant effect simultaneously on the intention to save.